The Analysis of Factors Influencing Hypertension on Elderly: A Literature Study - Ario Wahid Sauma; Isyeu Sriagustini; Sinta Fitriani; Wuri Ratna Hidayani; Leni M. Malabanan (Journal of Public Health Sciences, 2022)
The prevalence of hypertension disease year after year continues to increase. The impact of hypertension and its risks in addition to two affecting human survival and reducing work productivity also adds to the burden of health service costs. Efforts to control this disease are not possible only by the health sector but must involve other sectors and active community involvement. The purpose of this study is to examine a journal of factors that influence the incidence in the elderly. This research method is descriptive analytics using a literature review design. The conclusion of this study is derived from ten research journals. The most dominant factors that influence the incidence of hypertension in terms of behavior include smoking, salt consumption, coffee consumption, and physical activity.